An Extra Slice of Jo Brand. Issue 2 (1st June 2015) - Lockyer, Sharon
Abstract : In this candid interview Jo Brand, one of Britain's most popular and successful comedians, discusses her comedy career. Brand shares experiences and critical reflections on a wide range of comedy, from her first stand-up gig in the 1980s through to presenting the Great British Bake Off: An Extra Slice (2014– present). She discusses the inspiration and motivation for her comic material, explains the highs and lows of working in television comedy and offers pragmatic advice for comedians wishing to pursue a career in comedy today.